مساهمة مؤسسات التأمين التكافلي في تحقيق التنمية المستدامة تجارب دولية ماليزيا . المملكة العربية السعودية . الجزائر - هاجر, زربيط; سعاد, عين; عفاف, بن علي (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة إلى تسليط الضوء على مساهمة مؤسسات التأمين التكافلي في تحقيق التنمية المستدامة من خلال أن مؤسسات التأمين التكافلي توفر منتجات تأمينية متنوعة لدعم مختلف الأنشطة الاقتصادية ومن ثم دعم التنمية المستدامة, مع الإشارة إلى تجارب دولية ماليزية ,المملكة العربية السعودية, الجزائر, وقد تم استخدام المنهج الوصفي التحليلي لمعالجة دور مؤسسات التأمين التكافلي في تحقيق التنمية المستدامة. وتوصلت الدراسة, أن هناك جهود مبذولة لدولة ماليزيا في مجال التأمين التكافلي لتعزيز التنمية المستدامة, أما مملكة العربية السعودية فتوصلت الدراسة إلى التزام بتطبيق القوانين المنظمة لقطاع التأمين التكافلي، بالإضافة إلى هيمنة التأمين الصحي والمركبات على القطاع بسبب الإقبال الإجباري للأفراد على هاتين الخدمتين، أما بالنسبة لتجربة الجزائر من خلال شركة سلامة للتأمينات أوضحت أن هذه الصناعة لا زالت تعاني من عدة صعوبات أهمها غياب إطار قانوني منظم ,ونقص الثقافة التأمينية.""This study aims to shed light on the contribution of Takaful insurance institutions to achieving sustainable development through that Takaful insurance institutions provide a variety of insurance products to support various economic activities and then support sustainable development, with reference to Malaysian international experiences, Kingdom of Saudi Arabia, Algeria. Using the descriptive analytical approach to address the role of Takaful insurance institutions in achieving sustainable development. The study found that there are efforts made by the State of Malaysia in the field of Takaful insurance to promote sustainable development, while the Kingdom of Saudi Arabia has reached a commitment to apply the laws regulating the Takaful insurance sector, in addition to the dominance of health and vehicle insurance over the sector due to the compulsory demand of individuals for these two services. The experience of Algeria through the Salama Insurance Company made it clear that this industry still suffers from several difficulties, the most important of which is the absence of an organized legal framework, and the lack of insurance culture."
ماستر اقتصاد
Keywords: تأمين تكافلي، مؤسسات تأمين التكافلي، تنمية مستدامة، ثقافة تأمينية.; Takaful insurance, Takaful insurance institutions, sustainable development, insurance culture.